The Role of High-Performance Work System Practices in Organizational Performance: The Mediating Role of Employees’ Engagement and the Moderating Role of Servant Leadership: Evidence from the Airline Industry - Afeshat, Rawan Al (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The purpose of this study was to examine the mediating role of employee engagement in the relationships of High-Performance Work System (HPWS) practices with organizational performance. Additionally, it investigated the impact of HPWS practices on organizational performance. Also, it studied the moderating role of servant leadership on the relationship between employee engagement and the organization performance in airline sector in Jordan. The respondents in the current study were 277 employees working in the private airline sector in Jordan during the two-month period of January and February 2018. The results of the study revealed that an HPWS practice was positively linked with organizational performance as demonstrated by better employee satisfaction and employee retention. Moreover, the findings indicated that employee engagement partially mediates the relationships of HPWS practices with employee satisfaction and employee retention. Finally, the results revealed that the moderating role of servant leadership is not significant on the relationship between employee engagement and organizational performance. This study is the first empirical study of the airline sector in Jordan and the first to focus on employee engagement possible mediating role in the effect of HPWS practices on employee satisfaction and employee retention using Structural Equation Modeling (SEM) to analyze data collected from employees working in the airline sector. Future studies should move beyond individual performance parameters such as employee satisfaction and employee retention to test the influence of HPWS practices on performance at the organizational level, such as financial performance. Keywords: HPWS practices, employee engagement, employee satisfaction and employee retention, servant leadership.

ÖZ: Çalışmanın amacı havayolu şirketlerinde Yüksek Performanslı Çalışma Sistemleri uygulamalarının kurum performansı ile ilişkisine çalışan angajmanı etkisinin değerlendirilmesidir. Bunun yanında, Yüksek Performanslı Çalışma Sistemlerinin kurum performansı üzerindeki doğrudan etkisi de incelenmektedir. Ürdün havayolları sektöründe hizmetkar liderlerin çalışan angajmanı ve kurum performansını ne şekilde değiştirdiği de araştırılmıştır. Ürdün özel sektör havayolları firmalarında çalışmakta olan 277 çalışandan Ocak – Şubat 2018 tarihlerinde toplanan anket verileri kullanılmıştır. Sonuçlar Yüksek Performanslı Çalışma Sistemlerinin kurumsal performansa çalışan tatmini ve kalıcılığını artırarak katkıda bulunduğunu ortaya koymaktadır. Sonuçlar çalışan bağlılığı Yüksek Performanslı Çalışma Sistemleri ile kurum performansı ilişkisine aracılık yaptığını göstermektedir. Hizmetkar liderliğin daha yüksek olduğu durumlarda ise çalışan katılımı ile çalışan tatmini kalıcılığı ile ölçülen kurumsal performans arasında ilişkinin daha etkili olduğu belirlenmiştir. Çalışma Ürdün havayolları şirketleri üzerinde çalışan angajmanı Yüksek Performanslı Çalışma Sistemleri, iş tatmini, kalıcılığı ilişkilerini Yapısal Eşitlik Modeli yöntemi ile inceleyen ilk ampirik çalışmadır. Gelecekte araştırmacılar bireysel tatmin ve işte kalıcılığı ötesinde kurumsal performansı ölçecek makro göstergeler kullanarak birey ve kurum düzeyleri arasındaki ilişkiyi de incelemelidir. Anahtar Kelimeler: Yüksek Performanslı Çalışma Sistemleri, Çalışan angajmanı, Çalışan Kalıcılığı, Hizmetkar Liderlik
Doctor of Philosophy in Tourism Management. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Tourism, 2019. Supervisor: Prof. Dr. Cem Tanova.
Keywords: Tourism; Organizational behavior--Psychology, Industrial--Organizational effectiveness; High-Performance Work Systems--Airline Sector--Jordan; Work Attitudes--Job Satisfaction itizenship--Organizational Climate; Human Resources Management; HPWS practices; employee engagement; employee satisfaction and employee retention; servant leadership